The Runners' Repair Manual : A complete program for diagnosing and treating your foot, leg, and back problems - Weisenfeld, Murray F. frey50; Burr, Barbara (New York St. Martin's Press., 1980)
If you haven't started running yet, or you sort-of-started but stopped, then you've got an advantage over a lot of people. Most people don't consult a podiatrist until after they've been running a while - running wrong - and they've got an injury. Now, by reading this book, you're "seeing a podiatrist" before you start - so you can start running right.
Includes index.
Keywords: Foot -- Wounds and injuries; Running. -- Accidents and injuries; Athletic Injuries; Foot Injuries